2015
DOI: 10.1074/jbc.m114.603795
|View full text |Cite
|
Sign up to set email alerts
|

SH2B1 and IRSp53 Proteins Promote the Formation of Dendrites and Dendritic Branches

Abstract: Background: Filopodium formation is a prerequisite for neurite initiation. Results: SH2B1 interacts with IRSp53 and promotes neurite outgrowth of hippocampal neurons. Conclusion: SH2B1-IRSp53 complexes promote filopodium formation, neurite initiation, and neurite branching. Significance: These results suggest that SH2B1 may regulate the formation of filopodia required for many cellular functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…It has been reported that CDC42 and IRSp53 are both potential candidate substrates of PTP1B, and PTP1B was identified two times in our intracellular data. Functionally, both PTP1B and IRSp53 have been linked to dendritic filopodia‐like formation in neurons, and a recent proteomics study identified that the enrichment of IRSp53 in dendritic filopodia . There have been reports showing that HSV‐1 dramatically increases the formation of dendritic filopodia to facilitate viral spread in primary neurons .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CDC42 and IRSp53 are both potential candidate substrates of PTP1B, and PTP1B was identified two times in our intracellular data. Functionally, both PTP1B and IRSp53 have been linked to dendritic filopodia‐like formation in neurons, and a recent proteomics study identified that the enrichment of IRSp53 in dendritic filopodia . There have been reports showing that HSV‐1 dramatically increases the formation of dendritic filopodia to facilitate viral spread in primary neurons .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, JAK2 has been reported to be regulated by SH2B1 adapter protein 1 (Maures, Kurzer, & Carter‐Su, ), which is able to increase tyrosine kinase activity that is associated with cytokine receptors, such as JAK2. Interestingly, Chen et al () suggested that SH2B1 protein orchestrates signaling for dendrite formation and its branching, both in hippocampal neurons and in the PC12 neuronal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Sprague Dawley (SD) rats were purchased from BioLASCO Taiwan Co., Ltd. Primary cortical neurons were dissociated from dissected cortices of rat embryos (E18), seeded onto PLL-coated dishes and culture in vitro as previously described [48,49]. For the in vitro TBI model, cortical neurons were injured by scraping with a p20 tip to generate gaps over the culture on DIV8 ( Figure 1A).…”
Section: In Vitro Culture Of Primary Neurons and The Tbi Modelmentioning
confidence: 99%